Cancer Cell Targeting With Functionalized Quantum Dot-Encoded Polyelectrolyte Microcapsules - Nifontova, Galina; Ramos-Gomes, Fernanda; Baryshnikova, Maria; Alves, Frauke; Nabiev, Igor; Sukhanova, Alyona (Frontiers in Chemistry, 2019)
Imaging agents and drug carriers are commonly targeted towards cancer cell through functionalization with specific recognition molecules. Quantum dots (QDs) are fluorescent semiconductor nanocrystals whose extraordinary brightness and photostability make them attractive for direct fluorescent labeling of biomolecules or optical encoding of the membranes and cells. Here, we analyse the cytotoxicity of QD-encoded microcapsules, validate an approach to the activation of the microcapsule’s surface for further functionalization with monoclonal antibody Trastuzumab, a humanized monoclonal antibody targeting the extracellular domain of the human epidermal growth factor receptor 2 (HER2) and already in clinical use for the treatment of HER2 positive breast cancer. In addition, we characterize the cell-specific targeting activity of the resultant bio-conjugate by immunofluorescence analysis (IFA) and real-time analysis of interaction of the conjugates with live HER2 overexpressing human breast cancer cells. We demonstrate, that encapsulation of QDs into the polymer shell using the layer-by-layer deposition method yields highly fluorescent polyelectrolyte microcapsules with a homogeneous size distribution and biocompatibility upon in vitro treatment of cancer cells. Carbodiimide surface activation ensures optimal disperse and optical characteristics of the QD-encoded microcapsules before antibody conjugation. The prepared conjugates of the microcapsules with cancer-specific monoclonal antibody targeting HER2 provide sufficiently sensitive and specific antibody-mediated binding of the microcapsules with live cancer cells, which demonstrated their potential as prospective cancer cell–targeting agents.